Poland’s System: Contraction and Implications - Kwiek, Marek (My University, 2012)
In the near future, the decline of enrollment levels in Poland is expected to be the highest drop in Europe. There are two Organization for Economic Cooperation and Development scenarios for Poland. First, enrollments in 2025 are expected to fall to 55 percent of the 2005 levels or dwindle by almost a million students (947,000). Or, second, based on trends, they are expected to fall to 65 percent of the 2005 levels or decline to almost 800,000 students (775,000). In none of the other European systems will demographic shifts lead to shrinking student populations to a comparable degree. The decrease in student numbers is expected to fall from 1.82 million (2010) to 1.52 million (2015), to 1.25 million (2020).
Keywords: Poland; Polish higher education; private sector; public-private; private sector decline; demographics; fees; private sector future; Central Europe; Eastern Europe; postcommunist; public services; higher education policy; demograhic scenarios